Identifying detour patterns of rail feeder bus routes: A city-scale analysis - Enhui Chen; Zhitong Sun; Keyu Ji; Jing Teng (Journal of Transport Geography, 2026)

Optimizing demand-responsive feeder transit stop locations for transportation hubs: A multi-objective approach - Tong Wu; Jing Teng; Enhui Chen (Journal of Transport Geography, 2026)

From multi-omics insights to single-strain proof: How traditional agricultural system enhances fish flavor via the microbiome-gut-muscle axis - Xiaoqiang Shen; Xiaoyu Lei; Huarui Zhang; Enhui Guo; Lichao Chen; Chao Sun; Abrar Muhammad; Yongqi Shao (Bioresource Technology, 2026)

The Coupling Coordination and Spatio-temporal Evolution of Water-energy-food in the Yellow River Basin - Ken Sun; Xinyu Chen; Jiacheng Liu; Enhui Shi; Yuanbiao Wang; Yiting Zhou; Xiaotong Xing; Jiabin Chen (Water, Air, & Soil Pollution, 2026)

Coupling coordination and spatiotemporal evolution of water and energy welfare performance in 35 cities of the Yellow River Basin, 2010–2019 - Ken Sun; Xiaotong Xing; Jiacheng Liu; Enhui Shi; Yuanbiao Wang; Yiting Zhou; Xinyu Chen (Environment, Development and Sustainability, 2026)

Unveiling the occurrence and ecological risks of phthalate esters in the municipal wastewater treatment plant by a specific fragment-based GC-EI&PCI-HRMS method - Yinuo Xiao; Kun Wang; Jinsong Liu; Jing Wang; Zhengzheng Liu; Qinqin Sun; Chaoming Zhang; Enhui Wu; Jiahui Yang; Baoliang Chen (Water Research, 2026)

MnO₂ polymorphs direct the selective degradation of fluoroquinolone antibiotics: Insights from adsorption, oxidation, and O₂ activation mechanisms - Ruohan Zhao; Enhui Wu; Xiangyu Zhu; Xinfei Ge; Xin Xiao; Baoliang Chen (Chemical Engineering Journal, 2026)

Complete genome sequence of watermelon silver mottle virus infecting Momordica charantia L. in China - Zhongshan Chen; Enhui Li; Lele Cai; Duanxiang Xu; Wenli Du; Xiaolin Zeng; Fangluan Gao; Shan Gao (Australasian Plant Pathology, 2026)

A novel compound nutrition powder ameliorates scopolamine-induced cognitive impairment via activating the PKA/CREB/BDNF signaling pathway and restoring cholinergic function - Xiaomeng Xu; Zihan Yuan; Enhui Ma; Limin Zhong; Dong Chen; Songyi Lin (Food Bioscience, 2026)

Sesquiterpenoids with anti-neuroinflammatory effects in vitro from Laggera alata - Xingxi Li; Wenhao Qiao; Qian Yang; Mingzhu Hu; Enhui Wang; Rongping Zhang; Xinglong Chen (Phytochemistry Letters, 2026)

Enhanced photodynamic therapy induces dual nuclear/mitochondrial DNA damage and cGAS/STING-driven innate immunity for improved colorectal cancer immunotherapy - Dexiang Zhu; Weijun Huang; Yutong Wang; Yuxiao Yang; Fanghua Su; Chuyue Lu; Zhenyu Lin; Enhui Zhou; Zhian Chen; Ruiyuan Liu; Qianbing Zhang (Chemical Engineering Journal, 2026)

Fate, bioaccumulation, and toxic responses of PFOA, PFOS, and GenX in the paddy soil–rice system across the full growth cycle - Wantong Tang; Xin Xiao; Enhui Wu; Kun Wang; Xinfei Ge; Xiaoying Zhu; Chiheng Chu; Baoliang Chen (Journal of Hazardous Materials, 2026)

Strengthening coordination for electrolyte diluent via dipole polarization enables rapid Na+ solvation/desolvation kinetics - Yan Meng; Yuanheng Wang; Qingjiang Liu; Xingyu Chen; Enhui Wang; Weihua Chen; Hongji Pan; Jinghao Zhao; Xin Li; Jia-Yan Liang (Chemical Engineering Journal, 2025)

Appraisal and strategic allocation of industrial water use efficiency in henan province: balancing economic and ecological environmental objectives - Ken Sun; Xiaotong Xing; Weisheng Xie; Zhenzhen Yang; Jingmin Han; Yuanbiao Wangas; Jiacheng Liu; Enhui Shi; Jiabin Chen (Environment, Development and Sustainability, 2025)

A review of weed image identification based on deep few-shot learning - Enhui Wu; Yu Chen; Ruijun Ma; Xiande Zhao (Computers and Electronics in Agriculture, 2025)

Diversity Analysis of Microbial Communities in Shrimp Polyculture Ponds in Coastal Saline–Alkali Regions of Hebei, China - Enhui Suo; Zhao Chen; Huan Gao; Shijia Yuan; Zhiqiang Chang (Fishes, 2025)
To investigate the structure and successional dynamics of microbial communities in shrimp culture ponds in coastal saline–alkali regions of Hebei, China, we compared the water microbiota of Litopenaeus vannamei monoculture ponds and L. vannamei–Macrobrachium rosenbergii polyculture ponds in the early, mid, and late culture stages. The results revealed clear temporal succession patterns in both the diversity and composition of microeukaryotic and bacterial communities. Distinct differences were also observed between the two culture models. Compared with monoculture, polyculture ponds showed 2.23–34.76% lower abundances of parasitic microeukaryotes, such as Rozellomycota and Perkinsida. In contrast, the abundances of carbon- and nitrogen-cycling bacterial groups (e.g., LD29, CL500-29_marine_group) and Chlorophyta were 0.24–50.94% higher in the polyculture system. Co-occurrence network analysis showed that polyculture enhanced competitive interactions and increased the network structural complexity within bacterial and cross-domain microbial networks. These findings help elucidate the mechanisms underlying efficient shrimp production in saline–alkali ponds and support the optimization of aquaculture models.

Soil oxygen fluctuations as a natural barrier against antibiotic resistant genes propagation: Indications from bacterial network and community assembly - Huicong Yan; Xiangyu Zhu; Yajing Wu; Enhui Wu; Xiaomin Zhu; Baoliang Chen (Journal of Hazardous Materials, 2025)

Revealing the pivotal role of B/N-co-doping onto carbon nanospheres for promoted sulfamethoxazole degradation and its bio-toxicity evaluation - Jing Wang; Enhui Jiang; Mingyang Jia; Baosong Xing; Chen Fang; Haoqi Wang; Jiaying Yan; Chuanying Pan; Xiang Liu; Xianyong Lan (Journal of Environmental Chemical Engineering, 2025)

K-modified cyano-rich carbon nitride for photocatalytic production of water treatment agent - Hydrogen peroxide in two-phase system - Yanhe Li; Zelin Ma; Yi Yang; Xia Li; Enhui Gao; Qiming Zhao; Xiao Chen; Hao Zhang (Journal of Water Process Engineering, 2025)

Spatial confinement of Co-N/O nanocatalyst into hollow carbon nanosphere for water purification and its biotoxicity assessment - Chen Fang; Yangyang Bai; Lingyuan Ma; Yejun Pan; Kun Pang; Jiaying Yan; Jiajun Song; Enhui Jiang; Haiyu Zhao; Chuanying Pan; Xiang Liu; Xianyong Lan (Chemical Engineering Journal, 2025)

Critical role of the support in the aqueous hydrogenation of 5-hydroxymethylfurfural to 2,5-bis(hydroxymethyl)furan over Pt-based catalysts - Hongli He; Jie Yang; Bo Kang; Mingxin Lv; Enhui Du; Zhilin Chen; Weiping Xie; Liyuan Huai; Hualei Hu; Chunlin Chen; Jian Zhang (Fuel, 2024)

A Comparative Study of the Effects of Extrusion on Lignocellulose Structure and Biogas Production from Wheat Straw and Digested Wheat Straw - Guangyin Chen; Hainan Cao; Changping Zhao; Wanrong Zhang; Jiawei Zheng; Enhui Wang (BioEnergy Research, 2023)

Use of a wheat straw covering to reduce nitrogen loss during pig slurry storage and reuse of the straw covering in biochar production for nitrogen retention in the slurry - Guangyin Chen; Pei Wu; Jinzhu Dong; Jiawei Zheng; Enhui Wang (Waste Management, 2023)

Novel nitrogen removal process in marine aquaculture wastewater treatment using Enteromorpha ferment liquid as carbon - Yiming Yu; Guanghui Chen; Deshuang Yu; Yanling Qiu; Songjie Li; Enhui Guo (Bioresource Technology, 2023)

Development of a spectrum-based ship fuel sulfur content real-time evaluation method - Hao Wu; Chao Wang; Enhui Chen; Zhirui Ye (Marine Pollution Bulletin, 2023)

The contribution of earthworms to carbon mineralization during vermicomposting of maize stover and cow dung - Yuxiang Chen; Yan Zhang; Xiong Shi; Enhui Shi; Tingting Zhao; Yi Zhang; Lixin Xu (Bioresource Technology, 2023)

PHR1 positively regulates phosphate starvation-induced anthocyanin accumulation through direct upregulation of genes F3’H and LDOX in Arabidopsis - Zhongjuan Liu; Xueqian Wu; Enhui Wang; Yanan Liu; Yi Wang; Qinghua Zheng; Yizhen Han; Zhongze Chen; Yongqiang Zhang (Planta, 2022)

The non-negligibility of greenhouse gas emission from a combined pre-composting and vermicomposting system with maize stover and cow dung - Lei Zhang; Tingting Zhao; Enhui Shi; Zunhao Zhang; Yan Zhang; Yuxiang Chen (Environmental Science and Pollution Research, 2021)

Toxicity bioassays for water from black-odor rivers in Wenzhou, China - He DeFu; Chen RuiRui; Zhu EnHui; Chen Na; Yang Bo; Shi HuaHong; Huang MinSheng (Environmental Science and Pollution Research, 2015)